“I Can’t Believe I Phubbed Up Our Friendship!”: Examining Relationships between Loneliness, Problematic Smartphone Use, Friend Phubbing, and Life Satisfaction - Juhyung Sun; Norman Wong (Human Behavior and Emerging Technologies)
As one of the dark sides of smartphone use, phubbing (i.e., snubbing others during face-to-face interactions by using their smartphones) has drawn increased attention in recent years. A growing literature on phubbing has widely examined psychological and social problems related to phubbing. However, very little is known about how certain psychological states and outcomes—mainly loneliness and life satisfaction—occur in relation to phubbing. This study examined the relationships between loneliness, problematic smartphone use, phubbing, and life satisfaction, particularly within friendships. For this study, college students (N=513; 188 men, 323 women, and two others) aged 18 to 29 (Mage=19.85 years) completed self-report measures online. Structural equation modeling was used to measure the model, and the relationships of this study were conducted via SPSS and AMOS. As expected, the model yielded a good fit, and the findings showed that loneliness positively and indirectly predicted the enactment of friend phubbing through its influence on problematic smartphone use, which negatively predicted life satisfaction.